Efficacy and Safety of PD-1/PD-L1 Inhibitor Versus Chemotherapy in First-line Treatment of Advanced Non-small Cell Lung Cancer: A Meta-analysis - WEI Yu; ZHANG Li (Zhongliu Fangzhi Yanjiu, 2019)
Objective To review the effectiveness and safety of PD-1/PD-L1 inhibitor versus chemotherapy in the first-line treatment of advanced non-small cell lung cancer. Methods Relevant literatures were searched through Web of Science database, ASCO meeting abstract, journals, etc. for meta-analysis. Results Totally 7 RCTs including 4101 patients were analyzed. The meta-analysis showed that compared with chemotherapy, PD-1/PD-L1 inhibitor combined with chemotherapy significantly prolonged PFS (HR=0.59, 95%CI: 0.59-0.70, P < 0.00001), OS (HR=0.65, 95%CI: 0.65-0.92, P=0.02) and ORR(RR=1.72, 95%CI: 1.13-2.62, P=0.01). Subgroup analysis showed PD-1/PD-L1 inhibitor combined with chemotherapy could significantly prolong PFS and OS, compared with chemotherapy. The higher PD-L1 expression was, the more significant the curative effect was. There was no statistical significance in prolonging PFS (HR=0.87, 95%CI: 0.57-1.31, P=0.50), OS (HR=0.82, 95%CI: 0.65-1.03, P=0.09) or increasing ORR (RR=1.12, 95%CI: 0.55-2.28, P=0.76) between single-agent PD-1/PD-L1 inhibitor and chemotherapy. Compared with chemotherapy, single-agent PD-1/PD-L1 inhibitor in the first-line treatment could significantly prolong the OS of advanced NSCLC patients with high PD-L1 expression. Grade 3-4 treatment-related adverse effect was not statistically significant different between PD-1/PD-L1 inhibitor combined with chemotherapy group and chemotherapy group (HR=1.09, 95%CI: 0.99-1.20, P=0.09), while that in single-agent PD-1/PD-L1 inhibitor group was lower (RR=0.43, 95%CI: 0.36-0.52, P < 0.00001). Conclusion Compared with chemotherapy, PD-1/PD-L1 inhibitor combined with chemotherapy in the first-line treatment on advanced NSCLC patients is more effective; single-agent PD-1/PD-L1 inhibitor should be used as the first-line treatment preferentially on advanced NSCLC patient with high PD-L1 expression.